Echinoclerodane A: A New Bioactive Clerodane-Type Diterpenoid from a Gorgonian Coral Echinomuricea sp - Cheng, Ching-Hsiao (Molecules, 2012)
A new clerodane-type diterpenoid, echinoclerodane A (1), was isolated from a Formosan gorgonian coral Echinomuricea sp. The structure of 1 was elucidated by spectroscopic methods. Echinoclerodane A (1) is the first clerodane-type compound obtained from the marine organisms belonging to the phylum Cnidaria. Echinoclerodane A (1) exhibited moderate cytotoxicity toward MOLT-4, HL-60, DLD-1 and LoVo tumor cells and inhibitory effects on the generation of superoxide anion and the release of elastase by human neutrophils.